Analysis of Scale of Business in mediating Financial Technology and Knowledge Management on Digital-Based Accounting of Micro, Small and Medium Enterprises in Medan City - Wirda, Ayu; Honkley, Tony; Suhendri, Suhendri (Jurnal Akuntansi Hukum dan Edukasi, 2024)
Micro, small and medium enterprises are businesses that can help neraga in improving the community's economy, reducing unemployment so that the government is now very enthusiastic in supporting the development of MSMEs. It is inseparable from the local government of Medan City which motivates business actors in using digitalisation in every sector in running a business so that it can develop not only at the national level but even at the international level. This research was conducted in Medan City with the variables used were Scale of Business, Finalcial Technology with Knowledge Management as the mediating variable on digital-based accounting of MSMEs. The population in this study were MSMEs under the guidance of the Medan City UKM cooperative office which already had a Business Identification Number of 488 businesses with a sampling method using the Slovin formula with an error rate of 5%. The analysis model used to test the hypothesis in this study is multiple regression analysis using the Smart PLS application. multiple regression analysis is a statistical method used to determine the magnitude of the influence between independent variables. Indirectly Scale of Business Mediates Financial Technology, on Digital-Based Accounting, Indirectly Scale of Business does not Mediate Knowledge Management, on Digital-Based Accounting, Directly Scale of Business, Financial Technology, Knowledge Management, have a significant effect on Digital-Based Accounting, Directly, Financial Technology has a significant effect on Scale of Business, Directly, Knowledge Management does not have a significant effect on Scale of Business micro small and medium enterprises in Medan City.